1996
DOI: 10.1002/(sici)1099-0852(199612)5:5<346::aid-car291>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Child Abuse and Neglect inChina: What the Papers Say

Abstract: In order to gain an insight into attitudes towards child abuse in China, a review of a number of newspapers for a period of 3 months was carried out. There was a dearth of relevant stories in national papers, but more in the local type of newspaper read by the majority of Chinese. Overall there were few reports relating to child abuse, especially in the intrafamilial setting. Of particular note is the number of reports of neglect of children following divorce. Violence towards students by teachers also feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…In addition, the current study strengthens previous studies, which have indicated that the media tends to cover child maltreatment incidents in ways that emphasise dominant social stereotypes. For example, the coverage gives over‐representation to more extreme and bizarre incidents of maltreatment (McDevitt, ), and to cases in which the abuser is a stranger (Atmore, ; Cheit, ; Hesketh and Lynch, ; Kitzinger, ; Kitzinger and Skidmore, ) or someone outside the family (Mejia et al, ). These representations are not consistent with systematic reviews of the literature on child maltreatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the current study strengthens previous studies, which have indicated that the media tends to cover child maltreatment incidents in ways that emphasise dominant social stereotypes. For example, the coverage gives over‐representation to more extreme and bizarre incidents of maltreatment (McDevitt, ), and to cases in which the abuser is a stranger (Atmore, ; Cheit, ; Hesketh and Lynch, ; Kitzinger, ; Kitzinger and Skidmore, ) or someone outside the family (Mejia et al, ). These representations are not consistent with systematic reviews of the literature on child maltreatment.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies exploring child maltreatment media coverage indicate that the media tends to cover child maltreatment incidents in ways that emphasise dominant social stereotypes; over‐representation seems to be given to more extreme and bizarre incidents of abuse (Kitzinger and Skidmore, ; McDevitt, ), or cases in which the offender is a stranger (Atmore, ; Cheit, ; Hesketh and Lynch, ; Kitzinger, ; Kitzinger and Skidmore, ), demonstrating that much of the public coverage of CSA is ‘case‐based’ and episodic. Such showcasing may give the impression that CSA consists of isolated instances that happen in a vacuum, as if to suggest that they are not the outcome of broader social conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are some voices urging for attention to be paid to violence against children in the family (Bu 2003), the problem has not yet received an active response. Literature related to child abuse or maltreatment in China is even more scarce (Hesketh & Lynch 1996; Hesketh et al . 2000), and existing studies are mainly on the medical consequences of maltreatment on children.…”
Section: Reasons For Inadequate Public Concernmentioning
confidence: 99%
“…In China, there have been a small number of studies of child abuse involving direct surveys with children, adults retrospectively, or examining perspectives from newspapers, child health professionals and mothers experiencing domestic violence (Chen, 2008;Hesketh et al, 2000;Hesketh and Lynch, 1996;Kim et al, 2000;Liu and Chan, 1999;Luo et al, 2008). Of particular relevance here, Liu and Zhang (2002), in a retrospective study of violence while growing up, with a sample of married people, found 72 per cent reported having been beaten by parents.…”
Section: 'A Revised Law On the Protection Of Minors 2006 Came Into Fomentioning
confidence: 99%